Correlation of IL-1alpha and IL-4 gene polymorphisms and clinical parameters in idiopathic pulmonary fibrosis - Koziar Vašáková, Martina; Stříž, Ilja; Slavčev, Antonij; Jandová, Šárka; Dutka, Juraj; Teřl, Milan; Kolesár, Libor; Šulc, Jan (Scandinavian journal of immunology, 2007)
Idiopathic pulmonary fibrosis (IPF) is a serious disease characterized with progressive scarring of the lungs in which a genetic background is supposed. We have tested correlation of promotor regions of IL-1alpha and IL-4 gene polymorphisms with clinical parameters in IPF. We investigated the group of 30 patients with IPF. The correlations of vital capacity (VC) and diffusing capacity for carbon monoxide (DL(CO)), bronchoalveolar lavage (BAL) fluid cell counts and high resolution computed tomography (HRCT) alveolar and interstitial scores with different genotypes of IL-4 at (-1098), (-590) and (-33) positions and IL-1 alpha at (-889) position were tested. The PCR method was used for genotyping. The carriers of CT genotype at IL-1 alpha (-889) position had higher VC at the time of diagnosis. The CC genotype at this position was more frequent in patients with higher counts of HLADR+ T lymphocytes in BAL. The GT genotype at IL-4 (-1098) position correlated with higher counts of CD4(+) T lymphocytes, and inversely the TT genotype with higher counts of CD8(+) T lymphocytes in BAL fluid. According to dynamic changes of HRCT score the CT genotype at IL-4 (-33) was more frequent in patients with progressive disease compared to that with stable disease. We assume from our data that the gene polymorphisms of the promotor region of IL-4 at position (-1098) and (-33) and IL-1 alpha at position (-889) are likely to play a pathogenic role in IPF and in modification of its clinical presentation and severity.
Keywords: respirační funkční testy; Interleukin-1alpha; polymerázová řetězová reakce; Male; počítačová rentgenová tomografie; Genetic Predisposition to Disease; Pulmonary Fibrosis; Genotype; polymorfismus genetický; Adult; Aged; dospělí; promotorové oblasti (genetika); mužské pohlaví; senioři; interleukin-4; Polymorphism, Genetic; Interleukin-4; plicní fibróza; Tomography, X-Ray Computed; vitální kapacita; senioři nad 80 let; lidé; ženské pohlaví; Humans; Bronchoalveolar Lavage Fluid; Promoter Regions, Genetic; Respiratory Function Tests; Aged, 80 and over; Financing, Organized; interleukin-1alfa; genotyp; Polymerase Chain Reaction; bronchoalveolární lavážní tekutina; Female; financování organizované; lidé středního věku; Vital Capacity; genetická predispozice k nemoci; Middle Aged